Weekly earnings of men and women, 1940 (1940)
1940 1939-1945 "Weekly earnings of men and women, 1940" [EP0085], 1940 Using statistics from the Ministry of Labour Gazette, this chart shows the relative earnings of men and women in various industries in 1940. The chart is from 'Women and work' by Gertrude Williams [Nicholson & Watson, 1945]